The impact of urban family physician program on health service access and utilization in Iranian children and adolescents: Results of the national health services utilization survey in 2015 - Masoumeh Shoja; Negar Asaad sajadi; Sahand Riazi Isfahani; Zhaleh Abdi; Elham Ahmadnezhad; Akbar Fotouhi (مجله پزشکی دانشگاه علوم پزشکی تبریز, 2024)
Background. The Urban Family Physician Program (UFPP) has been implemented in Fars and Mazandaran provinces of Iran since 2013 with the aim of improving access and utilization of health services, with a particular focus on children and adolescents. In order to evaluate the effectiveness of the program in achieving this goal, this study aimed to compare the access and utilization of health services among children living in areas covered by the UFPP with those living in other regions of Iran. Methods. A secondary analysis was performed using data from the 2015 National Health Utilization Survey. The data of people aged under 18 were extracted and indicators on the use of health services based on three main models of health service provisions were compared: (1) cities in Fars and Mazandaran provinces (UFPP implemented); (2) cities in other Iranian provinces (excluding Fars and Mazandaran); and (3) villages and cities with a population under 20,000. Results. The study included 20,689 children. The outpatient and inpatient visits in children living in Fars and Mazandaran provinces were higher than in children from other provinces and smaller towns (11.89 vs. 7.92 and 7.21 for outpatient and 4.74 vs. 3.51 and 4.27 for inpatient, respectively). Furthermore, UFPP was found to be associated with a higher utilization of health services in children residing in cities (odds ratio=1.50 (1.98-1.15)). Additionally, the cost of outpatient and inpatient health services in areas where the UFPP was implemented was lower compared to other parts of the country. Conclusion. The urban family physician program has been successful in increasing the access to health services and reducing health costs in children. Practical Implications. The findings suggest that the urban family physician program can be an effective strategy for improving healthcare access and reducing costs, especially in areas with high population density. Policymakers and healthcare providers can use the results of this study to inform the development and implementation of similar programs in other countries, with the aim of improving healthcare access and reducing healthcare costs in children and adolescents.